KOMODIFIKASI POLITIK KHUTBAH JUM’AT - Mutho'in Mutho'in (IAIN Pekalongan, 2015)
This Research discuse about how khutbah jum’at marginalize presidential candidate. By Critical linguistics approach introduced by Roger Fowler, the political nuances are not so obvious in khutbah, because the spirit of welcoming the fasting month is able to reduce the political heat. Nevertheless, there are two khubah jum’at that have potentially to marginalize presidential candidate, the first khutbah convey four criterias of Islamic leader but only focuses on amanah and the second khutbah invite to vote a leader who can be a prayer leader (imam shalat), even though presidential candidate attacked by black campaign with amanah and prayer leader issues.